Willingness-To-Pay for Estimation the Risk Pedestrian Group Accident Cost - Chompoonut Puttawong; Preeda Chaturabong (Salehan Institute of Higher Education, 2020)
The proven willingness-to-pay with contingent valuation (WTP-CV) method is an effective tool for evaluating the cost of road accidents in many countries. In Thailand, the most fatalities on Thailand’s roads involve the vulnerable road users (VRUs) including motorcycle users, bicyclists, and pedestrians. With the effectiveness of using WTP-CV in analyzing the accident cost of motorcycle users and lack of specific accident cost for pedestrians, this research focuses on evaluating the accident cost on the pedestrians which is the second most VRU fatality. In this research, the road accident cost of pedestrians aged 15-39 years in Bangkok by WTP-CV method was determined. The WTP-CV questionnaire was employed as a tool to measure the payment of which each pedestrian is willing to pay to reduce the fatality and injury risk from road accidents. One thousand and two hundred pedestrians in Bangkok were interviewed. With the results, the value of statistical life (VOSL) for pedestrians in Bangkok is valued at US 0.43 million, while the value of statistical injury (VOSI) is estimated at about US 0.014 million, respectively. In addition, it is found from the regression analysis that for the fatality risk reduction, higher educational levels and private business pedestrians are likely to pay more to save their lives. In order to reduce the risk of injury, respondents, who are single in marriage status, are likely to pay more to reduce the risk of pedestrian injury. However, a high perception of safety is less likely to pay for the reduction of injury risk.